Cervical Cancer Screening Cascade At Newlands Clinic By Dr Katayoun Taghavi, University Of Bern, Switzerland - Taghavi, Katayoun (My University, 2023)
This retrospective cohort study had aim to define and assess a cervical cancer screening cascade for women living with HIV enrolled at an ART clinic in Zimbabwe and to explore patient factors associated with retention through stages of the cascade. Main findings: Analysing outcomes along the proposed cervical screening cascade can identify areas for improvement; interventions are needed to improve linkage to treatment for screen-positive women who do not qualify for same-day cryotherapy; and many women continued to screen positive after treatment.
Keywords: cervical cancer; cervical cancer control cascade; cervical canceer screening